Board diversity, company’s financial performance and corporate social responsibility information disclosure in Malaysia - Hassan, Lily Suriana; Mohd Saleh, Norman; Ibrahim, Izani (International Business Education Journal, 2020)
The aim of this study is to investigate the relationship between board diversity, financial performance and disclosure of corporate social responsibility (CSR) information of the Malaysian listed companies. Different from prior literature, board diversity is viewed from the perspective of gender, age, tenure, educational level, professional membership and functional background. We used one explanation i.e. diversity as variety, out of three explanations from a typology in social psychological and organizational management fields. The sample consists of 205 companies listed on Bursa Malaysia. Using regression analysis, a significant positive relationship was noted between the functional backgrounds of directors and the companies’ financial performance. The result shows that boards should have diversity in their functional background. The other forms of board diversity such as gender, age, tenure, educational level and professional membership have been found not to influence companies’ financial performance. Board professional membership diversity was found to significantly increase the CSR information disclosure. However, other forms of board diversity were found not to influence the CSR information disclosure. These findings may suggest that corporate boards should have diversity in their functional background and professional membership in order to enhance companies’ financial performance and CSR information disclosure.